Analisis Kesulitan Belajar pada Materi Limit Ditinjau dari Kecemasan Matematika - Siti Zahara; Kurnia Rahmi Yuberta (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
This research is motivated by learning difficulties experienced by students and low learning outcomes in mathematics. The purpose of this research is to describe how the learning difficulties of students from each level of math anxiety. This research is qualitative descriptive research. The research subjects were students of class XI MIPA 2 at SMAN 1 X Koto Singkarak. There are two instruments in this study, the main instrument is the researcher himself and there are three supporting instruments, namely the math anxiety questionnaire, a test of learning difficulties, and an interview guide for learning difficulties. The data analysis technique used is data reduction, data presentation, and conclusions. The results of the study show that students who have high math anxiety tend to have difficulty using concepts, principles, and procedures. Students who have moderate math anxiety tend to have difficulty learning to use principles and procedurals and some have difficulty learning concepts and procedurals. Students who have low math anxiety tend not to experience indicators of learning difficulties, on average students are able to complete test questions, it's just that subject 5 has difficulty with procedural indicators.